KETERAMPILAN MENULIS STRUKTUR DAN ISI TEKS PIDATO PERSUASIF SISWA KELAS X TB SMK PGRI 4 DENPASAR - Putu Dessy Fridayanthi; Melania Ngewo (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this study was to determine the skills, difficulties experienced and the factors that cause students to write skills in structure and content of persuasive speech text. The population in this study were all class X TB students of SMK PGRI 4 Denpasar in the 2020/2021 academic year, totaling 165 people from 4 classes. The sample in this study were students of class X TB SMK PGRI 4 Denpasar totaling 4 classes with a total of 62 students. In collecting data using the test method is the preparation of tests, implementation of tests, and scoring tests. The data processing method used in this research is descriptive statistical method. Based on these results it can be concluded. (1) The students' skills in writing the structure and content of persuasive speech text are good. (2) The difficulties faced by students in writing the structure and content of persuasive speech text, namely the title of the speech, the structure of the persuasive speech, the use of effective sentences, the choice of words, and the use of EYD. (3) The factors that cause difficulties experienced by students in writing the structure and content of a persuasive speech text can be seen from the results of interviews with 3 students each answering the use of effective sentences, good and standard word choices, and the use of EYD during the study.